2011
DOI: 10.1111/j.1600-0501.2010.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal ridge alterations after tooth extraction in the dog: flap vs. flapless surgery

Abstract: Evaluating ridge alterations in the vertical and horizontal dimension after 3 months of healing following tooth extraction, results for the flap and the flapless group were very similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…With respect to the impact of immediate loading on ridge alterations, our results are in agreement with those presented previously by Blanco et al. (b), where immediately loaded/immediate implants (test) were compared with unloaded non‐submerged immediate implants (control) after 3 months of healing. Results with respect to buccal bone resorption were 0.86 mm (test) and 1.3 mm (control) similarly to the M‐BC (buccal) distance of 1.17 mm (test) and 0.69 mm (control) obtained in this experiment, if we subtract the 1 mm corresponding to the prosthetic abutment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With respect to the impact of immediate loading on ridge alterations, our results are in agreement with those presented previously by Blanco et al. (b), where immediately loaded/immediate implants (test) were compared with unloaded non‐submerged immediate implants (control) after 3 months of healing. Results with respect to buccal bone resorption were 0.86 mm (test) and 1.3 mm (control) similarly to the M‐BC (buccal) distance of 1.17 mm (test) and 0.69 mm (control) obtained in this experiment, if we subtract the 1 mm corresponding to the prosthetic abutment.…”
Section: Discussionsupporting
confidence: 92%
“…Results from this experiment are in agreement with studies with a similar experimental design, but with one‐piece implants (Blanco et al. b, Liñares et al. ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…39 Moreover, during the initial phase of regeneration, the flap elevation performed to carry out tooth extractions and implant placement impairs the vascular supply to the healing site, hampering initial wound healing and possibly exerting a long-lasting effect in a dimensional reduction of the supporting bone. 40 Despite this, it was recently observed that a flapless approach in immediate implants did not substantially contribute to preventing alveolar bone resorption 41 ; hence, this issue should be addressed in future studies.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Hence, the edentulous ridge acquired a sloped, triangular outline (Araújo & Lindhe , ; Blanco et al. ).…”
mentioning
confidence: 99%